2010
DOI: 10.1007/s10658-009-9577-1
|View full text |Cite
|
Sign up to set email alerts
|

Light quality affects incidence of powdery mildew, expression of defence-related genes and associated metabolism in cucumber plants

Abstract: To determine whether light quality affects the incidence of disease, we exposed cucumber (Cucumis sativus L. cv. Jinyan No. 4) plants at the 4-leaf stage to white and other monochromatic lights and tested the effects on plant response to Sphaerotheca fuliginea, defence-related gene expression and metabolic changes. Exposure to red light resulted in higher levels of H 2 O 2 and salicylic acid (SA), and stronger expression of defence genes such as PR-1 than exposure to white or other monochromatic lights. In com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
82
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(89 citation statements)
references
References 34 publications
5
82
0
2
Order By: Relevance
“…The effects of blue and UV-A radiations on plant diseases are more variable and differ according to the pathosystem. For example, without UV-A or without blue wavelengths, light sources favor the development of the tomato mosaic virus disease in pepper but reduce the development of powdery mildew in cucumber (Schuerger and Brown, 1997;Wang et al, 2010b).…”
Section: Pathogen and Herbivore Resistancementioning
confidence: 99%
“…The effects of blue and UV-A radiations on plant diseases are more variable and differ according to the pathosystem. For example, without UV-A or without blue wavelengths, light sources favor the development of the tomato mosaic virus disease in pepper but reduce the development of powdery mildew in cucumber (Schuerger and Brown, 1997;Wang et al, 2010b).…”
Section: Pathogen and Herbivore Resistancementioning
confidence: 99%
“…Light, when compared with dark conditions, increases plant resistance to a variety of biotrophic pathogens (Zeier et al, 2004), and SA accumulation in healthy Arabidopsis plants has been shown to increase in response to increased PAR (Karpinski et al, 2003). Recent experiments with cucumber suggested that light-enhanced resistance may be specific for R, since other light treatments were less effective in reducing damage by Sphaerotheca fuliginea (powdery mildew) as compared with R irradiation (Wang et al, 2010). Infected plants responded with increased free SA levels, and this response, together with the induction of a range of SA-responsive genes, was enhanced in R as compared with other wavelengths (Wang et al, 2010).…”
Section: R:fr and Jamentioning
confidence: 99%
“…Recent experiments with cucumber suggested that light-enhanced resistance may be specific for R, since other light treatments were less effective in reducing damage by Sphaerotheca fuliginea (powdery mildew) as compared with R irradiation (Wang et al, 2010). Infected plants responded with increased free SA levels, and this response, together with the induction of a range of SA-responsive genes, was enhanced in R as compared with other wavelengths (Wang et al, 2010). The apparently specific effects of R suggest the involvement of phytochromes.…”
Section: R:fr and Jamentioning
confidence: 99%
“…It has been reported that red light, mainly perceived by Phytochromes (Pyr), is important for shoot growth including stem elongation on strawberries [11]. Wang et al [12] found that disease resistance to Sphaerotheca fuliginea in cucumber plants was induced by red light. On the other hand, blue lights are perceived by majorly two different receptor family, cryptochromes and phototropins.…”
Section: Introductionmentioning
confidence: 99%